An analysis of training requirements for practinioners of group therapy in therapeutic milieus - Moss-Morris, Valerie (Department of Social Development, 2023)
In order to assess the need to formulate training requirements for practitioners of group therapy in therapeutic milieus attached to the Cape Provincial Hospital service , the organization, theoretical framework and functioning of these therapeutic milieus have been cutline. The group therapy component of the therapeutic milieu programmes and the present training provider to all four psyct1iatric disciplines from whose ranks the co-therapists of the therapy groups nrc dravm have been examined . Within this framework an assessment of the need to provide bath improved training and some consider able training in common for the four psychiatric disciplines involved has been made. Evidence from U1e writer's observations reached during thrills' years or supervision of psychic social work students' group therapy in the therapeutic milieus together with examples from the students I process records has been cited to support the conclusion that these needs do exist. The training requirements have been analysed into four components: the theory, experiential group attcnd~1ce, group therapy practice, supervision. The formulation of a training programme embracing these components is advocated . It is concluded that the training programme 3hould to a great extent be applicable to co-therapists from the different psychiatric disciplines. Finally, a number of proposals as to hm-1 improved c1:1d common training programmes can be evaluated and implemented · have been outlined.